2021
DOI: 10.1111/imm.13392
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in pregnancy: New insights into innate and adaptive immune regulation

Abstract: The immunology of pregnancy has been the focus of many studies to better understand how the mother is able to tolerate the presence of a semi‐allogeneic fetus. Far from the initial view of pregnancy as a state of immunosuppression, successful fetal development from implantation to birth is now known to be under the control of an intricate balance of immune cells. The balance between pro‐inflammatory functions used to promote embryo implantation and placental development and immunosuppressive activity to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 113 publications
(168 reference statements)
1
21
0
2
Order By: Relevance
“…Fetal immune system development was a special process. Placental microenvironment and pregnancy hormones play a key role in shaping the phenotype, function, metabolism and transcription of neutrophils in UCB ( 21 , 22 ). They are the reasons for the different genotypes of neutrophils in UCB compared to healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal immune system development was a special process. Placental microenvironment and pregnancy hormones play a key role in shaping the phenotype, function, metabolism and transcription of neutrophils in UCB ( 21 , 22 ). They are the reasons for the different genotypes of neutrophils in UCB compared to healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are programmed to secrete pro-inflammatory cytokines and growth factors regulating decidua receptiveness and most importantly maternal resistance to embryo invasion [39]. It seems that cytokines orchestrate an immunological balancing between inflammatory and anti-inflammatory responses and are required for establishing maternal tolerance to the semi-allogenic fetus as well as for protecting both the mother and the fetus from infections throughout pregnancy [40,41]. Thus, many fetal, maternal, and placental mechanisms work simultaneously and synchronously establishing embryo-maternal communication in order to support embryo implantation and pregnancy establishment [42].…”
Section: Basic Immunological Characteristics Of the Endometrial Micro...mentioning
confidence: 99%
“…Single-cell transcriptomics revealed that decidualized assembloids harbored senescent subpopulations, and senescence in the stroma calibrated the emergence of anti-inflammatory decidual cells and pro-inflammatory senescent decidual cells, which controlled endometrial fate decisions at implantation and was closely correlated with RIF ( 15 ). Moreover, intricate immune regulation is one of the most crucial aspects for the successful implantation of the hemiallogenic embryo ( 16 , 17 ). Conversely, inappropriate immunocytes as well as immune function are implicated in RIF as evidenced by increasing high-quality studies ( 18 ).…”
Section: Introductionmentioning
confidence: 99%